Creative Branding Transforms School Management in Indonesia: Branding Kreatif Mengubah Manajemen Sekolah di Indonesia - Rizal, Sueb; Wahyuni, Hana Catur (Journal of Islamic and Muhammadiyah Studies, 2025)
General Background: Effective school management is crucial for creating quality, progressive, and advanced institutions, while inadequate planning can lead to poor management, teacher disengagement, and diminished reputation. Specific Background: Muhammadiyah 2 Bangil, an Islamic organization, is implementing innovative branding strategies to differentiate itself in the competitive Bangil educational environment. Knowledge Gap: Despite the growing trend of educational branding, limited research explores its impact on school management, community engagement, and overall school performance, particularly within Muhammadiyah schools. Aims: The study explores the impact of strategic planning and branding on school management, specifically examining the influence of "Sekolah Kreatif" branding at SMA Muhammadiyah 2 Bangil. Results: The findings indicate that the branding of "Sekolah Kreatif" has positively impacted the school's image, community engagement, and prospective student interest. The school has effectively communicated its value to internal stakeholders and the wider community, resulting in increased enrollment and a strengthened institutional identity. Novelty: The study offers fresh insights into the strategic use of branding in Islamic educational institutions, specifically in the context of Muhammadiyah schools. Implications: Strategic branding and effective school management can significantly improve a school's reputation, teacher motivation, and community relationships, serving as a model for other educational institutions. Highlights: Strategic Planning: Essential for achieving quality, development, and focused school management. Branding Impact: "Sekolah Kreatif" boosts reputation, enrollment, and distinguishes the school. Community Engagement: Strong stakeholder communication fosters positive school growth and image. Keywords: School management, strategic planning, Muhammadiyah education, creative branding, community engagement.